2011
DOI: 10.1002/chem.201100532
|View full text |Cite
|
Sign up to set email alerts
|

Generating Hydrogen Gas from Methane with Carbon Captured as Pure Spheroidal Nanomaterials

Abstract: Energy production by using hydrogen gas as a feedstock is considered to be one of the keys to creating clean energy, with the proviso that the gas is generated in a sustainable way with no emissions. A simple, self-sustaining process generating hydrogen gas from methane using inexpensive stainless steel wire-mesh catalysts at elevated temperatures (800 °C) is reported. A theoretical analysis of the production of electricity by this process revealed peak chain energy efficiencies up to 21% (emission free) when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…At the ambient pressure, the methane diluted in nitrogen (CH 4 /N 2 D 1/1, v/ v) was fed into the mesh catalyst at 800 C for 8 h for cracking to produce CNOs together with hydrogen. [15] The CNOs were purified by successive treatment of 70% HNO 3 and washed repeatedly with deionized water. [15,22,23] After filtering, the CNOs were calcined at 400 C under air atmosphere in a furnace to remove the amorphous carbon.…”
Section: Preparation Of Catalyst Fe/cnosmentioning
confidence: 99%
See 1 more Smart Citation
“…At the ambient pressure, the methane diluted in nitrogen (CH 4 /N 2 D 1/1, v/ v) was fed into the mesh catalyst at 800 C for 8 h for cracking to produce CNOs together with hydrogen. [15] The CNOs were purified by successive treatment of 70% HNO 3 and washed repeatedly with deionized water. [15,22,23] After filtering, the CNOs were calcined at 400 C under air atmosphere in a furnace to remove the amorphous carbon.…”
Section: Preparation Of Catalyst Fe/cnosmentioning
confidence: 99%
“…[11][12][13] The carbon onions offer a moderate specific surface area (500 m 2 /g) compared to that of carbon blacks and activated carbons, but this surface is fully accessible to ion adsorption due to an almost perfect graphite network with a high degree of curvature. [14] Recently, we have developed a chemical vapor deposition (CVD) method to largely produce CNOs, [15] which makes the utilization of CNOs as catalyst support viable. Precious metals supported on CNTs have been tested for NO decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…CNOs, which were synthesized by a methane cracking method, 8 were initially suspended in concentrated nitric acid (HNO 3 ) and ultrasonicated for 1 hour, followed by refluxing at 180 1C overnight to remove metallic impurities. The product was filtered, washed with Milli-Q water several times and then dried in an oven at 120 1C.…”
Section: Methodsmentioning
confidence: 99%
“…6 Decorating them with metal nanoparticles has also attracted considerable attention in heterogeneous catalysis and for use in high capacity Li-ion batteries where there is excellent cycling performance. 7 Recently we demonstrated that CNOs can be produced with a low-cost large-scale methane cracking method, 8 thereby laying down the foundation for the industrial uptake of this unique carbon nanomaterial. Furthermore, a vortex fluidic device (VFD) has been shown to produce CNOs-Pd and CNOs-Pt nanocrystalline hybrid materials for sensor and fuel cell applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation